Dollarization in Lithuania: An econometric approach - Igor Vetlov (Bank of Finland, Institute for Economies in Transition (BOFIT), 2001)
The paper analyses the factors driving dollarization in Lithuania during the period from December 1992 to August 2000.Starting with a brief overview of the major economic and political developments in Lithuania, the study attempts to model the process of dollarization by applying rigorous time series analysis.In particular, it investigates the long- and short-run properties of the relationship between the dollarization ratio and interest rates paid on domestic and foreign currency deposits.The study identifies a relatively stable cointegrating relationship between variables, whereby the dollarization ratio is negatively related to the interest rate spread.In the constructed vector error correction model, the deviations from the long-run relationship are found be significant for the dynamics of all three variables. Overall, the model explains the development of dollarization rather well.Simple specification of the model is possible when interest rates reflect the major economic and political events relevant to the process of dollarization.
URN:NBN:fi:bof-201408071993
Keywords: 330; dollarization; transition economy; currency board; unit roots; cointegration; vector error-correction